Effect of exercise order with barbell and machine modalities on upper body volume load and myoelectric activity - Bezerra, E. S.; Schoenfeld, B. J.; Paz, G.; de Araújo Farias, D.; Sakugawa, R. L.; Vieira, I.; Rossato, M.; Miranda, H. (Sports Biomechanics, 2020)
The purpose of this study was to investigate the influence of exercise order on volume load (VL) and myoelectric activation (EMG) during the bench press (BP), military press (MP) and close-grip bench press (CGBP) exercises executed with a barbell and Smith machine. Twelve men experienced in resistance training performed four different exercise sessions in randomised order. Each session consisted of four sets of a given exercise order: O1 = CGBP + MP + BP with barbell; O2 = inverse O1 with barbell, O3 = same O1 with Smith Machine; O4 = same O2 with Smith machine. EMG was assessed for the Clavicular head pectoralis major (PMC), anterior deltoid (AD), triceps brachii long head (TBLH) and biceps brachii (BB). Results showed that VL in BP was affected by exercise order, independent of the mode (p < 0.05). However, the CGBP showed higher VL in O1. Moreover, when the BP was positioned last in the sequence (O1 and O3), myoelectric activity was higher for PMC, AD and TBLH (p < 0.05). Findings were similar in the CGBP (PMC and TBLH), but for the AD (Smith machine > barbell, p < 0.05). Therefore, it appears that the order and modes of exercises influence both volume load and myoelectric activation patterns during multiple set of resistance training.